Mandibular Flexure in Anterior-Posterior and Transverse Plane on Edentulous Patients in Mashhad Faculty of Dentistry - Nafiseh Asadzadeh; Azam Sadat Madani; Seyyed Hadi Hosseini (Mashhad University of Medical Sciences, 2012)
Introduction: Angle and internal position of lateral pterygoid muscle leads to contraction over two half of the mandible in maximum opening and protrusion position so it can affects impression prosthetic procedures. The aim of this study was to evaluate the mandibular flexure in two transverse and antro-posterior dimensions. Methods: Seventy edentulous patients at Mashhad Faculty of Dentistry as the main group and 50 dentulous patients as the control group were selected. In these patients, transverse dimensions between second molar areas and also canine eminence from one side to another side, and longitudinal dimensions based on the distance between canine to second molar area at centric occlusion and maximum mouth opening were measured. Dimensional differences as the mandibular flexure were measured. Results: The mandibular dimensions in maximum opening and closed mouth were different. Average reduction in transverse dimension on second molar region at maximum mouth opening and closing position were almost equal to -0.0787 mm for target group and 0.7512 mm for control group. On anterior side, averages of these changes were equal to 0.3069 mm for target group and were 0.2254 mm for control group. Conclusion: Transverse dimensions in anterior region at maximum opening position are smaller than the same dimension at closed mouth in edentulous and dentulous patients.